The Position of Judges in the Indonesian Legal Idea - Moh. Mujibur Rohman; Elladdadi Mark; Kailie Maharjan (Rechtsnormen: Journal of Law, 2023)
Background. Judges are state judicial officials authorized by law to adjudicate. The role of judges is very important in the judicial order in Indonesia. Purpose. As we know, the Indonesian government system adheres to the trias politica, namely the legislative body as the legislator in this case the DPR, the executive body, namely the government and its cabinet and finally the judicial body, namely the judiciary. Method. The writing of this article cannot be separated from the name of the research method, because in scientific writing the method is a necessity which is the perfect and effective condition of a research result Results. In addition to the government system, the Indonesian legal system is known to follow the European-Continental legal system where the law will be based on the law or what is known as "law in book". Legal issues that are increasingly complex corner the enforcers of justice (read judges) are hit by many problems that are often not found in the law. Judges who must decide based on the law and on the other hand they cannot be absent from their profession in adjudicating, however they must decide for the sake of justice and human truth. Conclusion. In this article, the author seeks to explain the position of judges in finding law by writing articles using a qualitative and normative (doctrinal) approach as a type of research.